KNOWLEDGE AND ACTIONS FOR BREAST CANCER PREVENTION: ADVANCING AWARENESS AND PROMOTING EFFECTIVE PREVENTIVE PRACTICES - Ngjela, Juventina; Kociraj, Agim; Xhafaj, Delina; Qorri, Erda; Hilaj, Erina (South Eastern European Journal of Public Health, 2025)
Introduction: Breast cancer is among the most prevalent diseases affecting women globally, including in Albania. It represents a significant public health issue and remains a leading cause of mortality among women. The burden of breast cancer highlights the critical need for early detection and preventive strategies to mitigate its impact. Objective: This study aims to evaluate the level of awareness, knowledge, and behavioral responses regarding early indicators of breast cancer among Albanian women, focusing on the role of educational and preventive initiatives. Methods: A cross-sectional quantitative study design was employed using a standardized questionnaire. The survey was developed based on previous national and international research and disseminated online to a randomly selected sample of women across Albanian cities. A sufficiently large sample size was included to ensure broad demographic representation. Results: The findings indicated that 57% of participants believe that breast self-examinations should commence after the age of 20, despite recommendations advocating for earlier initiation. Approximately 52.8% reported receiving information about breast self-examination through awareness campaigns and healthcare professionals. Socioeconomic and educational factors were identified as significant determinants influencing women’s engagement with preventive measures and early diagnosis practices. Despite ongoing public awareness campaigns, knowledge gaps persist, and regular self-examination practices remain suboptimal among many participants. Conclusions: The study highlights the urgent need to enhance health education through targeted awareness campaigns and to improve access to preventive services for women in Albania. Promoting awareness of early symptoms and the benefits of early detection is essential to reducing breast cancer mortality rates and improving women's overall health outcomes.